AVENGERS : MILLENNIUM - Costa, Mike; Di Giandomenico, Carmine; Diaz, Paco; Cisic, Enis; Mossa, Andres (New York : Marvel Worldwide, 2015)
"At a secret Hydra installation hidden away in rural Japan, the Avengers discover a time-portal that sends them on an adventure that spans millennia. But what kind of bad guys have a time machine they don't use to change the past? Bad guys who know they win. Now the team must leap through time to figure out what kind of horrors Hydra have cooked up for the world, but something goes horribly wrong. Something always does. Plus: The Avengers are sent back to 1945 where they meet Cap and Bucky before the explosion that changed their lives forever. And later the team finds themselves in WWII Paris where Kang and the Grandmaster force them to battle the Invaders!"--Amazon.com
"Contains material originally published in magazine form as Avengers: Millennium #1-4 and Avengers #56 and #71."
Keywords: Avengers (Fictitious character) -- Comic books, strips, etc; Graphic novels